The Effect of Intercultural Competence and Stereotypes on International Student’s Social Anxiety and Psychological Adjustment - Srividya Karuturi (Universal Journal of Educational Research)
With an increased number of international students all over the world, intercultural competence has become an important concept to study. This basic idea of intercultural competence can be summed up as a person's capacity for understanding different cultures and having easy conversations with members of various cultures. A person needs to possess intercultural knowledge, attitude, skill, and awareness to be considered interculturally competent. Although the impact of intercultural competence has been studied, little study has been done on how individual factors affect social anxiety and psychological adjustment which are crucial for students who are assimilating into the new culture. The current study also looks at the preconceptions and intercultural competency that foreign students associate with Americans and how these preconceptions affect the psychological adjustment of the students about American society. The study adopts a quantitative survey method to investigate relationships. Through analysis, the study proves a positive relationship between intercultural knowledge, skill and attitude, and psychological adjustment among international students. Also, the research study positively interrelates stereotypes and intercultural competence.